The Impact of Chromebook Integration on Student Engagement and Learning Outcomes in a Rural Junior High School: A Case Study at Junior High School Satap 4 Sematu Jaya - Mudasir, Mudasir; Noor, Ady Ferdian (International Journal of Universal Education, 2025)
In the digital era, educational technology integration is becoming increasingly important, particularly in rural schools that lag in technology access and utilization. This study aims to analyze the impact of Chromebook use on student engagement and learning outcomes at SMP Satap 4 Sematu Jaya, a rural school that has recently adopted these devices. The research used a case study with data collection techniques through observation, interviews, document analysis, and questionnaires. Analysis was conducted qualitatively (thematic) and quantitatively (descriptive statistics). The results showed a significant increase in student engagement, both cognitively, emotionally, and behaviorally, after implementing Chromebooks. As many as 85% of students felt more motivated and were able to access digital learning resources that were previously unavailable. Average grades in Mathematics and Science increased by approximately 10% compared to before the use of Chromebooks. Furthermore, there was an increase in students' digital literacy, including the ability to search for information and collaborate online. However, the study also identified obstacles, such as limited internet access, a lack of teacher training, and inequality of access at home for students from low-income families. These findings confirm that Chromebook integration can improve engagement and learning outcomes in rural schools if supported by adequate infrastructure, teacher training, and equitable access. In conclusion, technologies like Chromebooks have the potential to narrow the education gap in remote areas, but their success requires implementation strategies that adapt to local conditions.